Approval of the Board of Regents to institutionalize the UP Open University Gender Focal Point System and create an Office of Gender Concerns - ---, --- (Review of Women's Studies; Vol 24 No 1-2 (2014): Review of Women's Studies Volume XXIV, Numbers 1-2 (January-December 2014), 2023)
---